2017
DOI: 10.15252/embj.201695273
|View full text |Cite
|
Sign up to set email alerts
|

AMPKα1‐LDH pathway regulates muscle stem cell self‐renewal by controlling metabolic homeostasis

Abstract: Control of stem cell fate to either enter terminal differentiation versus returning to quiescence (self-renewal) is crucial for tissue repair. Here, we showed that AMP-activated protein kinase (AMPK), the master metabolic regulator of the cell, controls muscle stem cell (MuSC) self-renewal. AMPKα1 MuSCs displayed a high self-renewal rate, which impairs muscle regeneration. AMPKα1 MuSCs showed a Warburg-like switch of their metabolism to higher glycolysis. We identified lactate dehydrogenase (LDH) as a new func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
96
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(103 citation statements)
references
References 86 publications
(201 reference statements)
6
96
0
1
Order By: Relevance
“…One key question is then to what extent this metabolism change might be necessary 458 for erythroid cells to differentiate, and if it might drive cells into the differentiation 459 process, as it has been proposed for other cell types [4,[43][44][45]. Our finding regarding 460 erythroid cells also support this hypothesis.…”
supporting
confidence: 69%
See 1 more Smart Citation
“…One key question is then to what extent this metabolism change might be necessary 458 for erythroid cells to differentiate, and if it might drive cells into the differentiation 459 process, as it has been proposed for other cell types [4,[43][44][45]. Our finding regarding 460 erythroid cells also support this hypothesis.…”
supporting
confidence: 69%
“…We further dissected 43 OXPHOS mechanisms by analyzing cell respiration response to different respiratory 44 chains inhibitors. Finally, LDHA role in erythroid progenitors self-renewal was assayed 45 using known molecular inhibitors and the CRISPR/Cas9 knock-out technology. Then, 46 to investigate whether LDHA downregulation could be responsible for metabolic state 47 changes in erythroid progenitors, we measured MMP of self-renewing cells following 48 inhibition of LDHA activity.…”
mentioning
confidence: 99%
“…Overall, numerous studies have identified a positive correlation between MuSC oxidative capacity and several aspects of MuSC function including cell number and muscle regenerative activity [22][23][24] . Several recent reports have delineated mechanisms that connect key tricarboxylic acid (TCA) cycle intermediates with transcriptional and epigenetic changes important for the function of MuSCs in muscle regeneration [25][26][27][28][29] . Indeed, cellular metabolism has been linked to quiescence, self-renewal, and differentiation function in other tissue-specific stem cell systems as well [30][31][32][33] .…”
Section: Introductionmentioning
confidence: 99%
“…On top of this, the novel capacity of cancer cells to adopt progenitor phenotype with metabolic reprogramming attracts substantial attention of researchers . In human cancers including HCC, the glycolytic signature of cancer stem cells have been portrayed in previous studies . Being a key regulator of hepatocyte differentiation, whether GATA6 is also responsible for rewiring cell metabolism in HCC still awaits investigation.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 In human cancers including HCC, the glycolytic signature of cancer stem cells have been portrayed in previous studies. 18,19 Being a key regulator of hepatocyte differentiation, whether GATA6 is also responsible for rewiring cell metabolism in HCC still awaits investigation. In this study, we carried out an indepth interrogation of the functional significance of GATA6 in HCC with reference to tumorigenicity, self-renewal, metastatic potential and metabolic phenotype.…”
Section: Introductionmentioning
confidence: 99%